A bioengineer in the city - the Darwinian fitness of fiddler crabs inhabiting plastic pollution hotspots (2023)
ABSTRACT: Mangrove forests have been widely recognized as effective traps for plastic litter, which tends to accumulate in landward areas. In mangrove forests surrounding cities, plastic litter may increase up to two orders of magnitude. Therefore, crabs that process sediments for feeding and burrowing in landward areas are likely to be impacted by marine litter and other disturbances. As counterintuitive as it may seem, crabs are developing dense populations in urban mangroves from different countries, suggesting parallel adaptive processes related to the availability of anthropogenic food sources. To better understand this, we compared the loads of macroplastics within and between mangroves along an urban-rural-wild forest gradient in the Uraba ´ Gulf, Colombian Caribbean. We then assessed if there is directional selection on crab phenotypes likely associated with human-provided food sources in urbanized forests. Finally, we evaluated the hypothesis that crabs in urban areas exhibit increased fecundity and survival - components of the Darwinian fitness - of female crabs in urban (versus wild) populations through three spawning seasons. Crabs in urban areas were larger (males), showed a healthier body condition (both sexes), and females had a larger reproductive lifespan than crabs in wild areas, strongly suggesting responses to the availability of predictable anthropogenic food subsidies in urban forests. Despite this, higher female fecundity was observed only during a spawning season. However, this short-lived increase in fecundity was offset by reduced survival among female crabs in urban forests, likely due to increased predation by birds, which appear to be emerging as dominant consumers in urban mangroves.